22)
1/sinx + 1/sin(x - 3π/2) = 4sin(7π/4 - x)
ta có: sin(x - 3π/2) = -sin[π - (x - π/2)] = -sin(x - π/2) = sin(π/2 - x) = cosx
đk: sinx ≠ 0, cosx ≠ 0 --> sin2x ≠ 0 --> x ≠ kπ/2 (k ∈ Z) (*)
pt ⇔ 1/sinx + 1/cosx = 4sin[2π - (π/4 + x)]
⇔ (sinx + cosx)/sinx.cosx = -4sin(x + π/4)
⇔ (sinx + cosx)/sinx.cosx = -4.[ sinx.cos(π/4) + cosx.sin(π/4) ]
⇔ (sinx + cosx)/sinx.cosx = -2√2.(sinx + cosx)
⇔ (sinx + cosx).(1/sinx.cosx + 2√2) = 0
⇔ [ sinx + cosx = 0
. . .[ 1/sinx.cosx = -2√2
+) sinx + cosx = 0 --> sinx = -cosx --> tanx = -1
--> x = -π/4 + mπ (m ∈ Z): t/m đk (*)
+) 1/sinx.cosx = -2√2 --> 2sinx.cosx = -1/√2 --> sin2x = sin(-π/4)
--> [ 2x = -π/4 + n2π (n ∈ Z)
. . .[ 2x = 5π/4 + p2π (p ∈ Z)
--> [ x = -π/8 + nπ (n ∈ Z)
. . .[ x = 5π/8 + pπ (p ∈ Z) : 2 nghiệm này đều t/m đk (*)
Vậy pt đã cho có 3 họ nghiệm là ...